Fast, free-breathing, in vivo fetal imaging using time-resolved 3D MRI technique: preliminary results - Liu, Jing; Glenn, Orit A.; Xu, Duan (Quantitative Imaging in Medicine and Surgery; Vol 4, No 2 (April 30, 2014): Quantitative Imaging in Medicine and Surgery (Parallel and sparse MR imaging: methods and instruments——Part 2), 2014)
Fetal MR imaging is very challenging due to the movement of fetus and the breathing motion of the mother. Current clinical protocols involve quick 2D scouting scans to determine scan plane and often several attempts to reorient the scan plane when the fetus moves. This makes acquisition of fetal MR images clinically challenging and results in long scan times in order to obtain images that are of diagnostic quality. Compared to 2D imaging, 3D imaging of the fetus has many advantages such as higher SNR and ability to reformat images in multiple planes. However, it is more sensitive to motion and challenging for fetal imaging due to irregular fetal motion in addition to maternal breathing and cardiac motion. This aim of this study is to develop a fast 3D fetal imaging technique to resolve the challenge of imaging the moving fetus. This 3D imaging sequence has multi-echo radial sampling in-plane and conventional Cartesian encoding through plane, which provides motion robustness and high data acquisition efficiency. The utilization of a golden-ratio based projection profile allows flexible time-resolved image reconstruction with arbitrary temporal resolution at arbitrary time points as well as high signal-to-noise and contrast-to-noise ratio. The nice features of the developed image technique allow the 3D visualization of the movements occurring throughout the scan. In this study, we applied this technique to three human subjects for fetal MRI and achieved promising preliminary results of fetal brain, heart and lung imaging.